2005
DOI: 10.17221/3366-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Anti-yeast effects of some plant extracts on yeasts contaminating processed poultry products in Egypt

Abstract: A total of 60 random samples of fresh chicken burger, fillet, and luncheon (20 of each) were collected from markets at Tanta city. The average total yeast counts (cfu/g) in burger, fillet, and luncheon samples were 2.7 × 10 6 ± 1.1 × 10 6 , 2.1 × 10 5 ± 0.9 × 10 5 , and 1.4 × 10 7 ± 0.7 × 10 7 , respectively. A total of 158 yeast isolates of 23 species were isolated and identified. Candida, Cryptococcus, Debaromyces, Issatchenkia, Pichia, Rhodotorula, Saccharomyces, Trichosporon and Yarrowia species were recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A study of the agar disc diffusion method on S. cerevisiae and Rhodotorula sp. for onion oil and D. hansenii and S. cerevisiae for garlic oil confirmed the present investigation. Lemon and grapefruit oils displayed static activity against D. hansenii and S. cerevisiae (MIC 10–24 μl/ml, Table ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A study of the agar disc diffusion method on S. cerevisiae and Rhodotorula sp. for onion oil and D. hansenii and S. cerevisiae for garlic oil confirmed the present investigation. Lemon and grapefruit oils displayed static activity against D. hansenii and S. cerevisiae (MIC 10–24 μl/ml, Table ).…”
Section: Resultssupporting
confidence: 90%
“…The lowest fungistatic activity was found for onion and garlic oils containing biologically active organosulfur compounds . However, garlic oil is reported to possess antibacterial and antifungal activity due to diallylsulfide, diallyltrisulfide, diallyltetrasulfide action; the oil's effectiveness can differ, depending on the studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with those of Conner and Beuchat (1984) and Chouliara et al (2007), who reported the inhibitory action of oregano oil on growth of yeasts. Brr and Mahmoud (2005) also showed that thyme extract, consisting of carvacrol and thymol as major components like oregano, had an inhibitory effect on the growth of Candida albicans, Debaryomyces hansenii, and Saccharomyces cerevisiae.…”
Section: Microbiological Changesmentioning
confidence: 94%
“…Throughout history, cinnamon has been believed to have several health benefits such as reducing triglyceride, LDL, total cholesterol, (Blevins et al 2007) (Connell et al 2016), anti-yeast activity (Brr and Mahmoud 2005), anti-inflammatory action, anti-platelet aggregation, and improving blood circulation (Chung et al 2011). One other example is Silymarin, a flavonolignan complex mixture from milk thistle plant, is already used for treatment of liver diseases, which we used in this study as reference.…”
Section: Introductionmentioning
confidence: 99%